DSC and DC Conductivity of Bi2O3 · LiF · B2O3 Glasses. (29th January 2013) - Arora, Susheel; Kundu, Virender; Goyal, D. R.; Maan, A. S.
Abstract : Fluoroborate glasses with Bi2 O3 content and having compositions x Bi2 O3  · (40 - x )LiF · 60B2 O3 (x = 0, 5, 10, 15, and 20) are prepared using melt-quench technique. DSC characterization is carried out to observe glass transition temperature. Two such temperatures are observed for each of the reported samples. DC conductivity of the reported samples is studied with the variation in temperature from 313 K to 413 K by dividing this range into three regions, namely, low-, intermediate-, and high-temperature regions. DC conductivity responses for these temperature regions are explained using different conductivity models.